2012
DOI: 10.1074/jbc.m112.399808
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli Subtilase Cytotoxin A Subunit Specifically Cleaves Cell-surface GRP78 Protein and Abolishes COOH-terminal-dependent Signaling

Abstract: Background: GRP78 is aberrantly expressed on the surface of many different tumor cells where it functions as a growth factor-like receptor. Results: SubA cleavage of cell-surface GRP78 abrogates signaling initiated by ligation of the GRP78 COOH-terminal. Conclusion: SubA specifically cleaves cell-surface GPR78. Significance: SubA is a powerful tool that can be used to specifically probe the functions of cell-surface GPR78.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Of note, using a lactate dehydrogenase assay, we did not detect any apoptosis in MCs treated with either antibody (data not shown). The enzyme SubA is a cellimpermeable proteinase that selectively cleaves the C terminus of cell surface GRP78, whereas the SubA A272 mutant lacks proteinase activity and serves as a control for the active enzyme (27). In line with our previous results, SubA, but not the mutant form, attenuated HG-induced FAK and Akt activation ( Fig.…”
Section: Cell Surface Grp78 Is Required For Activation Of Fak and Aktsupporting
confidence: 90%
“…Of note, using a lactate dehydrogenase assay, we did not detect any apoptosis in MCs treated with either antibody (data not shown). The enzyme SubA is a cellimpermeable proteinase that selectively cleaves the C terminus of cell surface GRP78, whereas the SubA A272 mutant lacks proteinase activity and serves as a control for the active enzyme (27). In line with our previous results, SubA, but not the mutant form, attenuated HG-induced FAK and Akt activation ( Fig.…”
Section: Cell Surface Grp78 Is Required For Activation Of Fak and Aktsupporting
confidence: 90%
“…1E). By staining for the C terminus of GRP78, which is surface-exposed upon translocation to the cell membrane (21), we found that TERS CM provided a progressive translocation of surface GRP78 (sGRP78) that began on day 3 and persisted through day 5 (Fig. 1F).…”
Section: Resultsmentioning
confidence: 99%
“…The discovery that GRP78 can also localize to the cell surface under pathophysiologic conditions such as cancer, opens up new mechanisms whereby this protein may exert its pro-proliferative and anti-apoptotic function in cancer. Cellular proteins such as MTJ-1 and Par-4 have been reported to facilitate trafficking of GRP78 from the ER to the cell surface [29] , [45] ; however, their association with sGRP78 is context dependent [46] . Our studies on sGRP78 in model cell systems and in cancer cell lines studies uncovered several novel observations.…”
Section: Discussionmentioning
confidence: 99%